Determination of trace metals by underpotential deposition–stripping voltammetry at solid electrodes - Herzog, G.; Arrigan, Damien (Elsevier BV, 2005)
We introduce the behaviour and applications of underpotential deposition (UPD) and its combination with stripping voltammetry (UPD–SV) of metal analytes at solid-electrode surfaces as an important analytical strategy for trace-metal determinations. We review the principles of UPD together with model metal/electrode systems, and discuss analytical utility, including achievement of limits of detection (LODs) and applications to a variety of sample matrices. We present an approach to the alleviation of sample-matrix effects by using surface-protective disorganised monolayer coatings. Finally, we also present the outlook for UPD-SV as an electroanalytical tool.